Coaching the beautiful game: an actor-network theory study of sport coaching. Issue 3 (2nd September 2021) - Maclean, Jordan
ABSTRACT : Sport coaches continue to coach without reference to a conceptualisation of coaching. Indeed, coaching research has been caught in a chasm between process and practice conceptualisations, further widening the application of theory to practice. And coaches are often the protagonists in both of these accounts. Yet, as we will see, this is controversial for several reasons. Inspired by actor-network theory and the theory of the quasi-object (Serres, M. [1980] 2007. The Parasite . Minneapolis: Minnesota University Press), I go to the local, material, mundane sites where coaching is practiced and follow the ball (the 12th player!) in action. Three anecdotes are described: moving from the game towards a field of practice, to be seduced, and or not to be seduced. This article presents an innovative way of observing the coaching process that brings about new insights for how coaching is conceived, understood and practiced. I conclude with some implications of articulating the sociomaterialities for coaching education.